Lecturer's Teaching Strategy in Improving Higher- Order Thinking Ability of Islamic Education Students - Asri Karolina; Reni Melawati; Idi Warsah; Eka Yanuarti; Eka Apriani (STAI Hubbulwathan Duri, 2023)
Lecture activities as processes and requirements exist, following academic rules and curriculum in a study program. It suggests how much basic knowledge students are required to have. The aim is to help students cope with the growing growth of science and technology. For this, Mamou's thinking ability achieves the educational goal, which is for students able to solve problems with high levels of thinking. The research aims to find out and analyze the lecturers' strategy used in increasing the efficacy of higher-order thinking, as well as the inhibitor and support factors in increasing higher-order ability. The study involves qualitative methods. The subjects were lecturers of the study program for Islamic education. The data collection techniques used in this study are observation, interviews, and documentation. The data-analysis techniques used are data reduction, data display, and verification. The results show the lecturers' strategy used in perpetuating students' ability to higher-order thinking with active learning strategies, incubation, suspected problems, and BBL. While the retard factors of a student's low thinking ability are lack of reading and the way lecturers should always guide students. As for the supporting factors are Internet access, library, and curiosity.